The Effects of Regular Moderate Intensity Exercise on Oxidative Stress and Serum Prolidase Levels: A Comparative Study - Bülent Güneri; Özlem Ekiz; Metin Kılınç; Adem Doğaner (Türk Spor ve Egzersiz Dergisi)
Background The effects of exercise on oxidation state is still a controversial topic. Additionally, the relation between exercise and serum levels of prolidase enzyme has not been reported so far. We aim to compare sedentary and physically active individuals regarding the levels of oxidative stress biomarkers and prolidase enzyme. Materials and Methods Healthy individuals, 19-22 years old, were enrolled in this study, encompassing the exercise group (n=79) and the sedentary group (n=48). The serum levels of glutathione peroxidase (GPX), catalase, malondialdehyde, total antioxidant status (TAS), total oxidant status (TOS), and prolidase were assayed. Statistical analyses were applied to the findings. Results The groups demonstrate insignificant difference regarding the serum GPX (p=0.558) and catalase (p=0.628) levels. The serum levels of malondialdehyde (p lt;0.001) and prolidase (p lt;0.001) are significantly higher in the exercise group and sedentary group than the other group, respectively. The TOS and TAS levels are considerably higher in the exercise group (p=0.025) and sedentary group (p lt;0.001) than the other group, respectively. Statistical analysis demonstrates significant relationship between the prolidase and TAS levels in the exercise group (r=0.243, p=0.031). Conclusion The remarkably lower prolidase levels in the exercise group suggest decreased collagen turnover in physically active individuals. Oxidative stress appears to occur without compensation by enzymatic antioxidant mechanisms in young adults, involved in moderate intensity exercises. This study also indicates a correlation between the serum levels of prolidase and TAS in this population.